2018
DOI: 10.1016/j.bja.2018.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Blood lactate concentration and shock index associated with massive transfusion in emergency department patients with primary postpartum haemorrhage

Abstract: Point-of-care testing of lactate concentrations in the emergency department may be useful to predict massive transfusion requirements in primary postpartum haemorrhage. Combining initial lactate concentrations with the shock index improves the predictive performance for massive transfusion requirements and may contribute to rapid risk stratification of patients with primary postpartum haemorrhage in need of transfusion and further focus on early interventions to control bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
61
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(69 citation statements)
references
References 18 publications
1
61
0
7
Order By: Relevance
“…However, both studies included only women with PPH, with limited statistical analysis and fewer, less meaningful clinical outcomes. 14,27 Our research team previously performed two retrospective prediction studies to evaluate SI and conventional vital signs as predictors of adverse outcomes in women with PPH (high-and low-income settings) and to develop potential traffic light early-warning system thresholds for the CRADLE VSA. 12,13 The utility of SI in maternal sepsis has not previously been explored.…”
Section: Ta B L Ementioning
confidence: 99%
“…However, both studies included only women with PPH, with limited statistical analysis and fewer, less meaningful clinical outcomes. 14,27 Our research team previously performed two retrospective prediction studies to evaluate SI and conventional vital signs as predictors of adverse outcomes in women with PPH (high-and low-income settings) and to develop potential traffic light early-warning system thresholds for the CRADLE VSA. 12,13 The utility of SI in maternal sepsis has not previously been explored.…”
Section: Ta B L Ementioning
confidence: 99%
“…More blood transfusions were observed in the SPPH group compared to the non‐SPPH group, indicating that most of the patients with blood loss higher than 1500 mL may need a transfusion. Studies such as the one carried out by Lee et al, 27 Sohn et al, 28 and Hoskins and Berg 29 reported that a level of lactate higher than 4.0 mmol/L was associated with good specificity, sensitivity, and positive predictive value for massive transfusions in obstetric patients. Lactate from different samples such as the fetal scalp, amniotic fluid, and vaginal fluids has been used to detect fetal and maternal outcomes; however, none of them is applicable in cases of PPH due to the possible mixture of blood and other fluids during childbirth 30,31 …”
Section: Discussionmentioning
confidence: 96%
“…Another possible explanation for the inter-study discrepancy may be that septic shock in our patients was defined in accordance with the Sepsis-3 definition; thus, it included septic shock patients with more severe conditions and worse outcomes than those included in prior studies using outdated definitions of septic shock [27,28]. SI, calculated as HR divided by SBP, has been associated with early recognition and mortality of septic and hypovolemic shock [29][30][31][32]. In this study, however, the SIs in the patients with septic shock did not have a significant impact on survival outcomes.…”
Section: Discussionmentioning
confidence: 99%